2018
DOI: 10.3171/2017.4.jns162871
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension: 120-day clinical, radiological, and manometric outcomes after stent insertion into the dural venous sinus

Abstract: OBJECTIVE Idiopathic intracranial hypertension (IIH) is commonly associated with venous sinus stenosis. In recent years, transvenous dural venous sinus stent (DVSS) insertion has emerged as a potential therapy for resistant cases. However, there remains considerable uncertainty over the safety and efficacy of this procedure, in particular the incidence of intraprocedural and delayed complications and in the longevity of sinus patency, pressure gradient obliteration, and therapeutic clinical outcome. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…Some studies have suggested that longer stents or the use of more than 1 stent may reduce the risk of juxta-stent stenosis after venous stenting, especially in the setting of extrinsic compression or very high-pressure gradients [7]. A recent study by Asif et al [18] reported similar stent survival rates of 87% at 120 days. However, complications were slightly higher at 4.9% and efficacy for reduction of papilledema was lower (63% reduction) than in our study.…”
Section: Discussionsupporting
confidence: 49%
“…Some studies have suggested that longer stents or the use of more than 1 stent may reduce the risk of juxta-stent stenosis after venous stenting, especially in the setting of extrinsic compression or very high-pressure gradients [7]. A recent study by Asif et al [18] reported similar stent survival rates of 87% at 120 days. However, complications were slightly higher at 4.9% and efficacy for reduction of papilledema was lower (63% reduction) than in our study.…”
Section: Discussionsupporting
confidence: 49%
“…21 The appropriate cut-off has not been established to determine which patients are appropriate candidates for stenting, although most interventionalists have used a minimum TSG of 4 to 10 mm Hg. 6,[22][23][24][25][26] Some groups measure the TSG before and after lumbar puncture and do not proceed with stenting if the TSG resolves (suggesting an extrinsic stenosis), believing that only intrinsic stenosis plays a causative role in the disease. However, the positive feedback loop theory discussed earlier and evidence demonstrating efficacy of stenting in patients with both intrinsic and extrinsic stenosis (see later) support consideration of the procedure in both cases.…”
Section: Patient Selection For Stentingmentioning
confidence: 99%
“…In all, we found 808 cases of venous stenting performed for IIH, collated from 30 studies with four or more patients and 12 case reports or series with three or fewer patients. 6,10,20,22,23, Whenever possible, we excluded studies in which the majority of patients had already been reported on. A representative case is depicted in ►Fig.…”
Section: Safety and Efficacy Of Venous Stenting In Iihmentioning
confidence: 99%
“…Starke et al 40 reviewed 17 studies from 2002 to 2014 with 185 patients receiving VSS (Tables 2 and 3 in their report). 1,[3][4][5]7,9,10,14,17,18,21,24,29,31,32,35,36,41,45 The locations of stent placement were not included. The authors reported that 78.3% of patients presenting with headache experienced some relief or complete resolution following stent placement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…40 Others have reported re-vision rates with VSS as high as 13%. 2 While additional studies have shown lower complication rates with VSS than with shunting, 5 the clinical outcomes are not easily comparable, and a randomized, prospective study would provide the greatest evidence to determine the optimal treatment option.…”
Section: Literature Reviewmentioning
confidence: 99%